Run, jump, throw and catch: How proficient are children attending English schools at the fundamental motor skills identified as key within the school curriculum?. (November 2020) - Duncan, Michael J; Roscoe, Clare MP; Noon, Mark; Clark, Cain CT; O'Brien, Wesley; Eyre, Emma LJ
This study examined proficiency levels in fundamental motor skills (FMS) in children within Key Stage 1 and 2 of the English school system. Four hundred and ninety-two children aged 6–9 Years old (245 boys, 247 girls) from school Years Two ( n = 130), Three ( n = 154) and Four ( n = 208) participated in this study. FMS for the run, jump, throw and catch were assessed using the Test of Gross Motor Development – 2. The proportion of children who achieved mastery or near mastery of the skills was determined. For the whole sample, 18.5% ( n = 91) did not achieve mastery in any of the four skills. A similar proportion (18.7%, n = 92) achieved mastery in all four of the FMS examined in this study. The proportion of children achieving mastery of all four skills was lower for Year Two children (0%) compared to children in years Three (24%) and Four (25%). More boys (25.7%) achieved mastery in all four of the FMS compared to girls (11.7%). Individual behavioural components in skill performance were also examined. The results of the present study highlight that less than one-fifth of children aged 6–9 years old have mastered the four key FMS identified by the physical education (PE) curriculum despite having the developmental potential to become fundamentally competent by six years of age. Fostering positive trajectories of FMS development presents a challenge for PE specialists given the association between FMS mastery in childhood and physical activity, weight status and health.